2015
DOI: 10.1002/tox.22170
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of Kalanchoe tubiflora extract against human lung cancer cells in vitro and in vivo

Abstract: Uncontrolled cell proliferation is a common feature of human cancer. Some of herbal extract or plant-derived medicine had been shown as an important source of effective anticancer agents. We previously reported that an n-BuOH-soluble fraction of Kalanchoe tubiflora has antiproliferative activity by inducing mitotic catastrophe. In this study, we showed that the H O-soluble fraction of Kalanchoe tubiflora (KT-W) caused cell cycle arrest, and senescence-inducing activities in A549 cells. We used 2 dimensional PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…More recently, the water-soluble fraction of the same extract was shown to cause cell cycle arrest, and to induce senescence in lung cancer A549 cells. At doses of 10 mg and 100 mg/kg b. w. 5 times per week for 6 weeks, the fraction also reduced tumor growth in nude mice [89].…”
Section: Cytotoxic and Antitumor Promoting Activitymentioning
confidence: 90%
“…More recently, the water-soluble fraction of the same extract was shown to cause cell cycle arrest, and to induce senescence in lung cancer A549 cells. At doses of 10 mg and 100 mg/kg b. w. 5 times per week for 6 weeks, the fraction also reduced tumor growth in nude mice [89].…”
Section: Cytotoxic and Antitumor Promoting Activitymentioning
confidence: 90%
“…Ward, notoespècie que presenta un fort caràcter invasiu i que fou creada artificialment per l'horticultor A.D. Houghton als anys 30 als seus hivernacles de Califòrnia (Houghton, 1935). Kalanchoe destaca, a més a més, pel fet que alguns dels seus tàxons poden causar toxicitat en animals si són ingerits (McKenzie & Dunster, 1986;Smith, 2004), tot i que també s'han indicat possibles usos medicinals (Milad et al, 2014;Bogucka-Kocka et al, 2016;Hsieh et al, 2016).…”
Section: Introduccióunclassified
“…Lung cancer is the end result of lung carcinogenesis and is the leading cause of cancer death around the world; in Asia, more than 86,000 new lung cancer cases were diagnosed every year in Japan and 9,000 cases in Taiwan [Bioworld Asia estimates] (Landis et al, ; Lin et al, ; Wang et al, ; Hsieh et al, ; Siegel et al, ). Particularly in lung cancer, adenocarcinoma is one of the major histological types that show resistant to most of the drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Plants and medicinal fungus possess various bioactive components, therefore many plants have been investigated to identify their potential role as an antioxidants, cancer preventative and therapeutic agents (Aravindaram and Yang, ; Hsieh et al, ). Previous epidemiological studies have shown that the consumption of vegetables, fruits and tea is associated with a low risk of cancer (Block et al, ; Pandey and Rizvi, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation